Generalized roughness in (∈,∈∨q)-fuzzy ideals of hemirings - Muhammad Rameez; Muhammad Irfan Ali; Asad Ejaz (Kuwait Journal of Science)
Generalized roughness for fuzzy ideals in hemirings is studied. Approximations for fuzzy prime ideals are discussed. It is shown that generalized lower approximation as well as generalized upper approximation of (∈ , ∈∨q)-fuzzy prime (semiprime) ideals of hemirings are (∈ , ∈∨q) fuzzy prime (semiprime) ideals.